New graduate nurses’ experiences with and perceptions of their mental health and well-being during the COVID-19 pandemic: An interpretive description study protocol - Robin D. Burry; April Pike; Joy Maddigan; Peggy Rauman; Holly Burford; Joanne Smith-Young; Vernon Curran (PLoS ONE, 2025)
Background The COVID-19 pandemic has had a significant impact on healthcare workers. Healthcare workplaces are high stress environments placing care providers such as Registered Nurses at high risk for occupational stress injuries related to poor mental health. Currently, healthcare authorities rely on new graduate nurses to help fill gaps in staffing; however, novice nurses are especially vulnerable to workplace illnesses, with the recent pandemic contributing to this risk. Research is needed to understand new graduate nurses’ experiences and perceptions of their mental health and well-being as they transition to practice in the COVID-19 pandemic and the supportive resources they require to assist in contributing to healthy workplaces. Objectives 1) To explore new graduate nurses’ experiences and perceptions of their mental health and well-being as they transitioned to practice during the COVID-19 pandemic in Newfoundland and Labrador, Canada; 2) To understand new graduate nurses’ awareness and use of available mental health supports and resources during the COVID-19 pandemic; and 3) To identify strategies and resources to support new graduate nurses’ mental health and well-being as they transitioned to practice during a public health crisis. Methods An interpretive description research methodology will be used to conduct this study. The COnsolidated criteria for REporting Qualitative research (COREQ) checklist will be used to verify both the structure of the study and presentation of findings. Approximately forty semi-structured interviews will be conducted with new graduate nurses who worked in Newfoundland and Labrador in 2020, 2021 or 2022. Data collected will be analyzed using thematic analysis with descriptive statistics used to present demographic information. Results The results of this study will help inform changes to existing workplace programs and contribute to the development of new processes to support new graduate nurses’ mental health and well-being as they transition to practice during a public health crisis such as COVID-19.